Software piracy exposed - Craig, Paul.; Honick, Ron.; Burnett, Mark (Mark M.) (Rockland, MA : Syngress, 2005)
This book is about software piracy--what it is and how it's done. Stealing software is not to be condoned, and theft of intellectual property and copyright infringement are serious matters, but it's totally unrealistic to pretend that it doesn't happen. Software piracy has reached epidemic proportions. Many computer users know this, the software companies know this, and once you've read the Introduction to this book, you'll understand why. Seeing how widespread software piracy is, learning how it's accomplished, and particularly how incredibly easy it is to do might surprise you. This book describes how software piracy is actually being carried out. * This book is about software piracy--what it is and how it's done * This is the first book ever to describe how software is actually stolen and traded over the internet * Discusses security implications resulting from over 1/2 of the internet's computers running illegal, unpatched, pirated software.
Inside software piracy -- The history of software piracy -- The suppliers -- Crackers -- The release -- Sites -- The distribution chain -- The piracy scene -- Piracy and the law -- The future of piracy.
Includes index.
Keywords: Acquisition of computer software; Computer crimes; Computer security; Electronic books